PERFORMANCE INDICATORS OF CHANGES OF BLOOD COAGULATION DURING PREGNANCY IN WOMEN WITH TROMBOFILICESCIE STATES - Макаров, О.Г. (World of Medicine and Biology, 2016)
Women during pregnancy is a major risk for the development of antiphospholipid syndrome. The frequency of this symptom in this category patsientok is about 5%. Aim of this work was to determine the status of the system hemocoagulation homeostasis in pregnancy s thrombophilia in different periods of gestation. Study of the system of hemostasis was carried out in I, II and III trimester of gestation. Klinichno examined 32 pregnant women with laboratory-confirmed antiphospholipid syndrome (study group) and 30 women with normal pregnancy (control group). It was viyavleno persistent increase in coagulation potential, both procoagulant and the vascular-platelet hemostasis in a group of pregnant women with APS.
Keywords: hemostasis; thrombophilia; gestation; antiphospholipid syndrome